Studi Kritis Filsafat Ketuhanan Dalam Risalah Hayy Bin Yaqzhan Karya Ibnu Thufail - Fahmi, Zainal Fahmi (Program Studi Aqidah dan Filsafat Islam STISA Ash-Shofa Tasikmalaya, 2025)
During the Islamic Golden Age, many great thinkers emerged, one of whom was Ibn Tufail. He is recognized as one of the leading plulosophers of the medieval period. His thoughts are reflected in his work titled